Implementasi Metode Tahsin Binnadhor Dalam Pembelajaran Al-Qur’an Santri Putri di Pondok Pesantren Tahfidzul Qur’an Al-Asy’ariyyah Kalibeber Mojotenagah Wonosobo - Anjar Kurnia Adiningsih; Maryono Maryono; Salis Irvan Fuadi (Lembaga Pengembangan Kinerja Dosen, 2023)
This thesis aims (1) to find out the implementation of the tahsin binnadhor method in learning the Koran for female students at the Tahfidzul Qur'an Al-Asy'ariyyah Islamic Boarding School, Kalibeber, Mojotengah, Wonosobo. (2) to find out the characteristics of the implementation of the binnadhor tahsin method in learning the Koran for female students at the Tahfidzul Qur'an Al-Asy'ariyyah Islamic Boarding School, Kalibeber, Mojotengah, Wonosobo. (3) to find out the supporting and inhibiting factors for the implementation of the tahsin binnadhor method in Al-Qur'an learning for female students at the Tahfidzul Qur'an Al-Asy'ariyyah Islamic Boarding School, Kalibeber, Mojotengah, WonosoboThe type of research used is descriptive qualitative. Data collection techniques using observation, interviews, and documentation. The main subject of this study was the new students of Block F Putri PPTQ Al-Asy'ariyyah, totaling 24 students. Data analysis techniques using data reduction, data presentation, and verification.The results showed that the implementation of the tahsin binnadhor method in learning the Qur'an, the students came forward one by one in turn and were listened to by the ustdazah if something went wrong it would be corrected. Characteristics of the implementation of the tahsin binnahor method in learning the Qur'an, students who are fluent, fluent, good and correct in reading the Qur'an will be recommended to recite the Koran at the Dzuriyah PPTQ Al-Asy'ariyyah. Factors supporting the implementation of the tahsin binnadhor method in learning the Qur'an ustadzah have syahadah juz 'ama and bin nadzri, the availability of adequate facilities and infrastructure. While the inhibiting factor is the lack of motivation in the students themselves, the time is too short.